Splenomegaly in a Patient with a History of Pernicious Anemia; the Potential Therapeutic Effects of B12 Therapy - Lordi, Alexis; Ansari, Nida; Maroules, Michael; Manjegowda, Anusha (Case Reports in Hematology, 2022)
Splenomegaly is manifested by a variety of etiologies, one of which is macrocytic anemia. Macrocytic anemia has multiple causes in itself that include; folate (Vitamin B9) and Cobalamin (vitamin B12) deficiencies. In this case report, we present a patient with a history of pancytopenia, macrocytic anemia and vitamin B12 deficiency, who underwent a splenectomy. The differential diagnoses for the cause of the patient’s splenomegaly included: lymphoma, infiltrative disease, and idiopathic splenomegaly. The pathology report from the splenectomy did not reveal any evidence of lymphoma or infiltrative disease, however, it did mention vascular congestion of the spleen. In theory, vascular congestion, due to extramedullary hematopoiesis in the spleen or sequestration of blood cell lineages, could lead to pancytopenia. In prior visits to the hospital this patient was diagnosed with: splenomegaly, and macrocytic anemia due to pernicious anemia. A splenectomy puts one at increased risk for infection by encapsulated organisms, and is to be avoided if possible. There are few case reports and studies that show vitamin B12 therapy can potentially cause a reversal in the splenomegaly as well as a reversal in the pancytopenia and macrocytic anemia. We hope to show that the least invasive treatment for vitamin B12, vitamin therapy, can be of use and effective.